(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research aimed to evaluate the implementation of the Philippine Informal Reading Inventory (Phil-IRI) in enhancing reading comprehension among Grade 10 learners at Cabancalan National High School, Schools Division of Mandaue City, for the school year 2025–2026. The research focused on determining the effectiveness of Phil-IRI in improving reading comprehension and on designing appropriate intervention activities based on identified learner needs. The research explored the demographic profiles of both teachers and learners, the level of Phil-IRI implementation in terms of frequency and accuracy of administration, instructional use of results, teacher preparedness, material availability, and monitoring practices. It also examined learners’ reading comprehension across literal, inferential, and critical/applied levels. A descriptive-correlational method was used to analyze the relationship between the Phil-IRI implementation and reading comprehension outcomes. Findings revealed that 50% of the teachers were between 31–40 years old, female, had bachelor’s degrees, and limited Phil-IRI-related training. Students were mostly aged 15–16, with more females than males. Teachers agreed that Phil-IRI was generally well implemented, particularly in terms of frequency, instruction, and teacher readiness, although materials and monitoring required improvement. Learners demonstrated satisfactory reading comprehension, with the highest performance in critical and applied interpretation. A significant positive relationship was established between the level of Phil-IRI implementation and learners’ comprehension outcomes. The study concludes that Phil-IRI is an effective tool for improving reading comprehension when implemented consistently. It recommends enhancing teacher training, ensuring sufficient resources, and developing context-based reading interventions to support learners’ literacy development.